2021
DOI: 10.1007/s10010-021-00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerische Prozessauslegung zur gezielten Eigenspannungseinstellung in warmmassivumgeformten Bauteilen unter Berücksichtigung von Makro- und Mikroskala

Abstract: ZusammenfassungZiel dieser Arbeit ist die Einstellung eines vorteilhaften Druckeigenspannungsprofils in warmumgeformten Bauteilen durch intelligente Prozessführung mit angepasster Abkühlung aus der Schmiedewärme. Die Machbarkeit und das Potenzial werden an einem Warmumformprozess, bei dem zylindrische Proben mit exzentrischer Bohrung bei 1000 °C umgeformt und anschließend aus der Schmiedewärme im Wasser abgekühlt werden, aufgezeigt. Vorige Arbeiten zeigen, dass sich Zugeigenspannungen in den derartig umgeformt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Fig. 1: a) Spray cooling device with six independent nozzles that provides temporal and spatial control of the cooling process, taken from [17]. b) Cylindrical specimen in initial and final configuration, provided by IFUM.…”
Section: A) B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1: a) Spray cooling device with six independent nozzles that provides temporal and spatial control of the cooling process, taken from [17]. b) Cylindrical specimen in initial and final configuration, provided by IFUM.…”
Section: A) B)mentioning
confidence: 99%
“…Therefore, this contribution focuses on the use of a spray cooling device as shown in Figure 1a, which has shown promising results, see e.g. [16,17]. For the considered cooling route, only one nozzle is active, which applies the spray as mixture of water and air on the thick side of the component.…”
Section: Hot Bulk Forming Processmentioning
confidence: 99%
“…In this context, [26] showed that induced compressive residual stresses in regions of high tensile loading can improve the performance and extend the operating time. As showed in [16], cooling with a spray device with one nozzle directed to the thick-walled side seems promising in order to obtain the targeted stress state. The remaining stresses that occur inside the material as a consequence of the cooling of the cylindrical specimen with a spray are interpreted as macroscopic residual stress in absence of outer forces and if the temperature gradient vanishes, that is, if room temperatures is achieved in the complete component.…”
Section: Macroscopic Residual Stress Analysismentioning
confidence: 99%
“…After the heating step, the forming reduces the height of the specimen by approximately 50%. Previous works [5, 16–19] showed that the application of different cooling media (air, water, spray) or routes (various spray cones) leads to different residual stress states. It was found that a spray cooling with a mixture of water and air, that lasts for 300 s results in the targeted stress state showing compressive stresses in regions near the outer surface of the cylinder [16, 18].…”
Section: Hot Bulk Forming Processmentioning
confidence: 99%
See 1 more Smart Citation